A BI‐LEVEL DECISION MODEL FOR CUSTOMER CHURN ANALYSIS. (20th March 2013) - Gao, Ya; Zhang, Guangquan; Lu, Jie; Ma, Jun
<x xml:space="preserve">Abstract</x> This paper develops a bi‐level decision model and a solution approach to optimizing service features for a company to reduce its customer churn rate. First, a bi‐level decision model, together with its modeling approach, are developed to describe the gaming relationship between decision makers in a company (service provider) and its customers. Then, a practical solution approach to reaching solutions for the bi‐level‐modeled customer churn problem is developed. Finally, experiments and case studies are conducted to illustrate the bi‐level decision model and the solution approach.